2005
DOI: 10.1515/bc.2005.101
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB contributes to transcription of placenta growth factor and interacts with metal responsive transcription factor-1 in hypoxic human cells

Abstract: Placenta growth factor (PlGF) is a member of the vascular endothelial growth factor family of cytokines that control vascular and lymphatic endothelium development. It has been implicated in promoting angiogenesis in pathological conditions via signaling to vascular endothelial growth factor receptor-1. PlGF expression is induced by hypoxia and proinflammatory stimuli. Metal responsive transcription factor 1 (MTF-1) was shown to take part in the hypoxic induction of PlGF in Ras-transformed mouse embryonic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 40 publications
1
51
1
Order By: Relevance
“…Despite the several reports stating that the expression of PlGF is upregulated in vitro under hypoxic condition in endothelial cells [28, 29], fibroblasts [35], cardiomyocytes [27] and in cancer cell lines [36, 37], only occasional data are available on visualization of PlGF in vivo in tissues in which pathological angiogenesis or wound healing, and consequently hypoxia, occurs. This was due to absence of efficient anti-PlGF antibodies for IHC analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the several reports stating that the expression of PlGF is upregulated in vitro under hypoxic condition in endothelial cells [28, 29], fibroblasts [35], cardiomyocytes [27] and in cancer cell lines [36, 37], only occasional data are available on visualization of PlGF in vivo in tissues in which pathological angiogenesis or wound healing, and consequently hypoxia, occurs. This was due to absence of efficient anti-PlGF antibodies for IHC analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Ang II could stimulate the expression of hypoxia inducible factor-1α (HIF-1α) [43], and HIF-1α seems to be involved in the enhanced PlGF expression stimulated by hypoxia [19]. The hypoxia-inducible PlGF expression is mediated through NF-κB, metal-regulatory transcription factor-1(MTF-1) and the interaction between them [19].…”
Section: Discussionmentioning
confidence: 99%
“…The PlGF expression can be induced by hypoxia and various pro-inflammatory stimuli [18]. This induction is mediated via NF-kappa B and metal response transcription factor-1(MTF-1)[19]. However, the regulation of PlGF expression in vascular cells, and its mechanisms of action have received little attention in atherosclerosis research.…”
Section: Introductionmentioning
confidence: 99%
“…led to more increased PlGF levels. However, a relationship between MTF-1 and NF-B p65 in the hypoxic induction of PlGF transcription was not definitively observed (51).…”
Section: Discussionmentioning
confidence: 97%